Model of competitive activity of highly qualified decathlers - Ogandjhanov A. L. ,; Salamatov M.B. ,; Tsyplenkova E.S. ,; Loktionov S.E. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop a model of competitive activity of highly qualified decathletes, to formulate a technology for managing the training process of track and field all-round athletes based on the model. Methods and structure of the study. Instrumental research methods included analysis of documentary materials, video recording and video analysis, photodiode timing, and methods of mathematical statistics. Results and conclusions. Based on a statistical analysis of indicators of competitive activity in certain types of decathlon of the world's leading all-around athletes, a model of competitive activity of highly qualified male all-around athletes was formed. The model allows, based on a comparison of an athlete’s performance with model parameters, to analyze the results of a decathlete in individual events, to identify lagging and dominant types of an athlete. This creates opportunities for planning results in individual types of decathlon for the next macrocycle of training and, on this basis, programming the special training of a multi-athlete at the stages of the macrocycle.